2020
DOI: 10.1021/acs.orglett.0c02593
|View full text |Cite
|
Sign up to set email alerts
|

Iodolopyrazolium Salts: Synthesis, Derivatizations, and Applications

Abstract: The synthesis of iodolopyrazolium salts via an oxidative cyclization of 3-(2-iodophenyl)-1H-pyrazoles is described. The reaction is characterized by a broad substrate scope and various applications of these novel cyclic iodolium salts acting as useful synthetic intermediates are demonstrated, in particular in site-selective ring-openings. This was finally applied to generate derivatives of the anti-inflammatory drug celecoxib. Their application as highly active halogen bonding donors is shown as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 68 publications
(34 reference statements)
0
56
0
2
Order By: Relevance
“…38,39 Very recently, we were able to introduce iodolopyrazolium salts as a unique class of N-heterocycle-based iodolium salts. 40 In our initial report, we demonstrated their potential reactivity as XBdonors. Inspired by this initial, although only moderate activity, in XB catalysis, we herein want to use this structural motif and present the first systematic investigation of N-heterocyclic iod(az)olium salts (NHISs) in general and their successful application as highly reactive XB-donors.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…38,39 Very recently, we were able to introduce iodolopyrazolium salts as a unique class of N-heterocycle-based iodolium salts. 40 In our initial report, we demonstrated their potential reactivity as XBdonors. Inspired by this initial, although only moderate activity, in XB catalysis, we herein want to use this structural motif and present the first systematic investigation of N-heterocyclic iod(az)olium salts (NHISs) in general and their successful application as highly reactive XB-donors.…”
Section: Introductionmentioning
confidence: 91%
“…Halogen bonds are important intermolecular interactions which find widespread applications in crystal engineering, functional materials and in molecular recognition. [1][2][3][4][5][6][7][8][9] In recent years XB was found to be an innovative concept in organic synthesis and in this regard XBdonors have been established as versatile catalysts. [10][11][12] The vast majority of XB-donors are based on monodentate iodine(I) derivatives with either a polyfluorinated or a N-heterocyclic backbone, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[17] Nachdem Han und Liu über den Einsatz von Diaryliodoniumsalzen als Katalysatoren in einer Mannich-Reaktion berichtet hatten, [18] konnte unsere Gruppe zeigen, dass die katalytische Aktivität zyklischer Iodoliumsalze in einer Halogenidabstraktion und einer Diels-Alder-Cycloaddition auf XB zurückzuführen ist. [19] Weitere Halogenidabstraktionen wurden nachfolgend von Aoshima, [20] Nachtsheim [21] und unserer Gruppe (bei der Aktivierung einer Metall-Halogen-Bindung [22] ) verçffentlicht.…”
Section: Halogenbrücken (Xb) Beschreiben Die Nicht-kovalentenunclassified
“…[17] Nachdem Han und Liu über den Einsatz von Diaryliodoniumsalzen als Katalysatoren in einer Mannich-Reaktion berichtet hatten, [18] konnte unsere Gruppe zeigen, dass die katalytische Aktivität zyklischer Iodoliumsalze in einer Halogenidabstraktion und einer Diels-Alder-Cycloaddition auf XB zurückzuführen ist. [19] Weitere Halogenidabstraktionen wurden nachfolgend von Aoshima, [20] Nachtsheim [21] und unserer Gruppe (bei der Aktivierung einer Metall-Halogen-Bindung [22] ) verçffentlicht.In einigen dieser Reaktionen [19,22] zeigte der Iodoliumkatalysator eine vergleichbare Aktivität zu den "klassischen" zweizähnigen Iod(I)-XB-Donoren. Diese starke Leistung ist besonders erwähnenswert, da die Iod(III)-Derivate als einzähnige XB Donoren agieren (Abbildung 1, Mitte), auch wenn diese im Prinzip über zwei elektrophile Achsen verfügen.…”
unclassified
“…Further, the chemistry of cyclic iodonium salts has recently experienced growing development (Chatterjee and Goswami, 2017). As for just an emerging interesting compound, Nachtsheim et al investigated that the direct oxidative cyclization of 3-(2-iodophenyl)-1H-pyrazole to novel iodolopyrazolium salt 36 via in-situ formed N-heterocyclic stabilized hydroxyλ 3 -iodane (Boelke et al, 2020) (Figure 2A, Equation d). They also demonstrated that the copper-catalyzed ring opening of 36 with acetate followed by hydrolysis produced functionalized heteroaromatic biaryl 37 in 70% yield.…”
Section: Heteroaryliodonium Salts As Highly Reactive Pseudo-halidesmentioning
confidence: 99%